The Application of Thermochromic Liquid Crystal in Temperature Distribution Measurement of Human’s Palm Hand - Flaviana F; Risti Suryantari (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2015)
Temperature is one of the most important parameters that represent human’s health condition. Some conventional measurements have not been fully accurate, concise, and precise, so Thermochromic Liquid Crystal (TLC) material is required, that based on its structure of molecule characteristics has respond for alteration of local temperature that indicated by color gradation.The purpose of this research is to perform and to learn the application of TLC-based measurement system in the palm of human’s hands. The benefit of this study is the result of that subject’s temperature mapping provides some opportunities for patients with painful diabetic neuropathy, which lead to ulceration in their foot or hand. The method has been developed using TLC system based on Flaviana’s research in 2012 and with specific setting, hardware and software, in order to acquire image(s). This system utilizes an image processing method, hue of the image is used as parameter, based on mathematical morphology operation.